Concordance between pharmacotherapeutic complexity calculated and perceived by HIV+ patients with antiretroviral treatment - Mercedes Manzano-García; Reyes Serrano-Giménez; María de las Aguas Robustillo-Cortés; Ramón Morillo-Verdugo (Elsevier, 2019)
Objective: To determine the difference between the pharmacotherapeutic complexity index by Medication Regimen Complexity Index and it's perceived by patients through a visual analogue scale in patients HIV+ with antiretroviral treatment. Method: Prospective, observational study of patients HIV+ > 18 years of age with stable antiretroviral treatment in the last three months, followed tp by external consultations of pharmaceutical care between October´17 and February ´18. The main variable of the study was the concordance between the median of the score obtained in the pharmacotherapeutic complexity perceived by the patients using the visual analog scale whose range of values oscillates between 0-10, categorized in low complexity (0-1) and high complexity (2-10), and the median of the score obtained for the theoretical pharmacotherapeutic complexity using the Medication Regimen Complexity Index tool whose ranges of values oscillate between 1 and infinity, categorized in low complexity (0-11) and high complexity > 11. The overall complexity was calculated: antiretroviral treatment and concomitant treatment. Results: We included 236 patients in the study. There was a discrete concordance between the pharmacotherapeutic complexity perceived by the patients and that calculated according to the Medication Regimen Complexity Index tool (Cohen's Kappa index 0.203). The median of the Medica tion Regimen Complexity index of the total medication was 6 (interquartile range: 4-10) versus the median of the Complexity Index measured by visual analog scale of 2 (interquartile range: 0-4). Conclusions: Patients perceive a pharmacotherapeutic complexity lower than that calculated. Therefore, we must include the two scales in pharmaceutical care for a better understanding of the patient's perception.